Enhanced demand side management method in optimizing utilization of available power supply - Shafer, Muhammad Gary (2014)
Optimization of available power supply has become one of solutions to maintain continuity of electric power supply. In order to apply the solution, two essential issues to be considered are peak load and unused power. Peak load is condition when power usage exceeds peak load boundary. This condition causes power generator to operate at its limit and distress the power system. Unused power is excess of power from power generation that cannot be stored. Thus, it decreases efficiency of the power system. Demand Side Management (DSM) is a group of techniques in load management that focuses to tackle the issues. Direct Load Control (DLC) is one of the techniques in DSM method that handles peak load. This technique switches off some feeders in near real-time based on priority. In addition, this technique also applies scheduling mechanism to handle power payback phenomenon inherented in peak load. However, DLC technique does not consider unused power issue. Thus, this study combines DLC technique with proposed Dynamic Power Allocation (DPA) technique to consider the unused power issue. Combination of these two techniques is proposed as enhancement of DSM method to optimize utilization of available power supply. Simulation of power usage has been designed and experiment has been conducted. Two experiments were conducted: experiment that applies DLC technique only and experiment that applies combination of DLC and DPA techniques. To evaluate the performance of enhanced DSM method, load factor parameter is used. Load factor represents average power usage divided by maximum power usage at certain time period. Evaluation result shows that DLC technique only achieves 0.85 in terms of load factor. Moreover, load factor from enhanced DSM method is increased to 0.92. From the results, it can be concluded that the enhanced DSM method has achieved better optimization in utilizing the available power supply.